Combining personal diaries with territorial intelligence to empower diabetic patients. (August 2015) - Sebillo, Monica; Tortora, Genny; Tucci, Maurizio; Vitiello, Giuliana; Ginige, Athula; Di Giovanni, Pasquale
Abstract: Information is today recognized as a major source of benefit, for those who are able to properly create and manage it. With the advent of new computing, storing and networking technologies, transforming data into useful, 'marketable' information has become a major goal for companies, organizations and governments. The healthcare domain makes no exception. Governments and healthcare companies are paying increasing attention to patient-centered care and to its positive effects on business metrics, such as finances, quality, safety, satisfaction and market share. Appropriate information sharing and communication are then recognized to be one of the key factors for patient-centered care. In this paper, we propose an infrastructure for defining new processes to support a fruitful exchange of strategic information at the local level, which could encourage local dynamics and improve the relationships between ultimate users and the territory and vice versa. This is particularly relevant in the healthcare domain, so we have developed a mobile application to provide diabetic patients with personalized services based on a technology with a low level invasive impact, through the experimentation of new process models meant to share information and integrate software components. Such a special-purpose application is meant to improve care experience of diabetic patients while creating public value for services. This is achieved by a profitable combination of territorial knowledge with personal data and events available and processed on smartphones. Highlights: Analysis of emerging healthcare challenges in territory sustainable development. A software infrastructure to develop special-purpose mobile applications. The prototype of a mobile application for diabetes׳ self-management. A spatio-temporal aggregation of user-generated metadata with mobile generated data.